6
$\begingroup$

Question:

Let $x$ be a complex number such that $x^{2011}=1$ and $x\neq1$ then, compute the sum

$$S=\dfrac{x^2}{x-1}+\dfrac{x^4}{x^2-1}+\dfrac{x^6}{x^3-1}+\dots+\dfrac{x^{4020}}{x^{2010}-1}$$

My attempt:

$$x=(1)^{\frac{1}{2011}}\implies x=1,e^{\frac{2\pi i}{2011}},e^{\frac{4\pi i}{2011}},\dots,e^{\frac{2010\pi i}{2011}}$$

let, $\alpha= e^{\frac{2\pi i}{2011}},$ then roots of given equation are $x=\alpha,\alpha^2,\alpha^3,\dots,\alpha^{2010}$

also

$$\alpha^{2010}=\dfrac{1}{\alpha};\ \alpha^{2009}=\dfrac{1}{\alpha^2};\ \dots; \ \alpha^{1006}=\dfrac{1}{\alpha^{1005}}$$

now, we have to compute:

$$S= \dfrac{\alpha^2}{\alpha-1}+\dfrac{\alpha^4}{\alpha^2-1}+\dfrac{\alpha^6}{\alpha^3-1}+\dots+\dfrac{\alpha^{4020}}{\alpha^{2010}-1}$$

then, I combined first term and last term, similarly second term and second last term and so on in this way i ended up here

$$S=\dfrac{\alpha^{2}-\alpha^{-3}}{\alpha-1}+\dfrac{\alpha^{4}-\alpha^{-6}}{\alpha^2-1}+.........+\dfrac{\alpha^{2010}-\alpha^{-1006}}{\alpha^{1005}-1}$$

here i got stuck , somehow i just wanted to exploit the property that sum of all roots of unity (who itself are in G.P) is zero but I couldn't

please give me hint or provide right way to solve this question.

thank you!

edit:

I also tried taking logarithmic derivative of $f(x)=x^{2011}-1$ but no progress further

$\endgroup$
6
$\begingroup$

$$ \sum_{k=1}^{2010}\frac{x^{2k}}{x^k-1}=\sum_{k=1}^{2010}\left(1+x^k+\frac{1}{x^k-1}\right) \tag{1}$$ and the minimal polynomial of a primitive $2011$-th root of unity is $\frac{x^{2011}-1}{x-1}=1+x+x^2+\ldots+x^{2010}$.
By denoting the primitive $2011$-th roots of unity as $\zeta^1,\zeta^2,\ldots,\zeta^{2010}$, the RHS of $(1)$ equals $$ 2010-1+\sum_{k=1}^{2010}\frac{1}{\zeta^k-1}\tag{2}$$ with the last sum being the sum of the reciprocal of the roots of $\frac{(x+1)^{2011}-1}{x}$.
Vieta's formulas hence convert the RHS of $(2)$ into $$ 2009 - \frac{1}{2011}\binom{2011}{2} = 2009-1005=\color{red}{1004}.\tag{3}$$

$\endgroup$
  • $\begingroup$ Simple and convincing (+1). Though it would be probably consequent to explain $\sum x^k$ with Vieta's formulas as well. $\endgroup$ – user Mar 21 '18 at 22:25
  • $\begingroup$ @user: but it is not needed: $1+x+\ldots+x^{2010}$ vanishes at $x=\zeta$, hence $\zeta+\zeta^2+\ldots+\zeta^{2010}=-1$. $\endgroup$ – Jack D'Aurizio Mar 21 '18 at 22:28
  • $\begingroup$ That the sum vanishes immedeately follows as well from the fact that $a_{2010}=0$. :) $\endgroup$ – user Mar 21 '18 at 22:35
4
$\begingroup$

Supposing that $\zeta$ is a primitive $n$th root of unity we consider

$$f(z) = \frac{z^2}{z-1} \frac{n z^{n-1}}{z^n-1} = \frac{1}{z-1} \frac{n z^{n+1}}{z^n-1} = \frac{n}{z-1} \left(z + \frac{z}{z^n-1}\right) \\ = n \left(1 + \frac{1}{z-1} \right) \left(1 + \frac{1}{z^n-1}\right).$$

We seek $$S_n = \sum_{k=1}^{n-1} \frac{\zeta^{2k}}{\zeta^k-1}.$$

We have by inspection that

$$S_n = \sum_{k=1}^{n-1} \mathrm{Res}_{z=\zeta^k} f(z).$$

With residues summing to zero this implies

$$S_n = - \mathrm{Res}_{z=1} f(z) - \mathrm{Res}_{z=\infty} f(z).$$

For the first residue we note that

$$\frac{1}{z^n-1} = \frac{1}{n} \frac{1}{z-1} + \cdots$$

and the constant term is

$$\left. \frac{1}{z^n-1} - \frac{1}{n} \frac{1}{z-1} \right|_{z=1} \\ = \left. \frac{1}{z-1} \left(\frac{1}{1+z+\cdots+z^{n-1}} - \frac{1}{n}\right)\right|_{z=1}$$

which is by L'Hopital

$$\left. - \frac{1+2z+\cdots+(n-1)z^{n-2}}{(1+z+\cdots+z^{n-1})^2} \right|_{z=1} = - \frac{1}{2} (n-1) n \frac{1}{n^2} = - \frac{1}{2n} (n-1)$$

and we may write

$$f(z) = n \left(1 + \frac{1}{z-1} \right) \left(1 + \frac{1}{n} \frac{1}{z-1} - \frac{1}{2n} (n-1) \cdots\right)$$

so that the residue is

$$n \left( 1 + \frac{1}{n} - \frac{1}{2n} (n-1) \right) = n + 1 - \frac{1}{2} (n-1) = \frac{1}{2} n + \frac{3}{2}.$$

For the residue at infinity we find with $n\ge 2$

$$- \mathrm{Res}_{z=0} \frac{1}{z^2} f(1/z) = -n \mathrm{Res}_{z=0} \frac{1}{z^2} \left(1 + \frac{1}{1/z-1} \right) \left(1 + \frac{1}{1/z^n-1}\right) \\ = -n \mathrm{Res}_{z=0} \frac{1}{z^2} \left(1 + \frac{z}{1-z} \right) \left(1 + \frac{z^n}{1-z^n}\right) \\ = -n [z^1] \left(1 + \frac{z}{1-z} \right) \left(1 + \frac{z^n}{1-z^n}\right) = - n.$$

Collecting everything yields the closed form

$$\bbox[5px,border:2px solid #00A000]{ \frac{1}{2} n - \frac{3}{2}.}$$

This will produce $1004$ for $n=2011$, confirming the answer by @JackDAurizio that appeared first.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.